Recent Advances on the Prevention and Management of Rheumatic Heart Disease - Jiawen Zhang; Songhao Jia; Yuhe Chen; Jie Han; Hongjia Zhang; Wenjian Jiang (Global Heart)
The global burden of rheumatic heart disease (RHD) remains substantial, particularly in low-income countries, despite advancements in prevention and management strategies. This article emphasizes the strategies related to primordial prevention, primary prevention, and secondary prevention, including recent advancements in vaccine development, and discusses current challenges in management and future research directions. For treatment, it evaluates percutaneous mitral commissurotomy, mitral valve repair, and replacement, noting the advantages of individualized approaches based on patient conditions. Addressing RHD’s global burden requires equitable access to surgical treatments, robust healthcare systems, and sustainable strategies for prevention and care.